Implementasi Antenatal Care Terpadu di Puskesmas Mayangan Jogoroto Jombang - Ninik Azizah; Dewi Triloka Wulandari; Vivin Eka Rahmawati; Helmi Annuchasari; Yuni Widaryanti (Lembaga Pengembangan Kinerja Dosen, 2025)
Pregnancy examination or Antenatal Care is important to ensure that the pregnancy process can run well and detect abnormal pregnant women so that complications that may occur during pregnancy can be detected early and handled adequately. For this reason, efforts and actions are needed from all groups, both cross-sectoral and cross-programmatic, to play an active role in reducing maternal and toddler mortality rates. Quality, regular, and continuous Antenatal Care checks during pregnancy can determine the health status of pregnant women and babies born. The purpose is to find out the Implementation of the Integrated ANC Service Program at the Mayangan Jogoroto Jombang Health Center on May 14, 2024. The approach used is counseling and socialization about the implementation of government programs for every pregnant woman to carry out integrated Antenatal Care. The procedure for implementing activities is divided into three stages, namely the preparation stage, the implementation stage, and the evaluation and monitoring stage. The methods used are lectures, discussions, and questions and answers by the target. The media used is an integrated Antenatal Care leaflet which provides convenience in developing materials and making it easier to explain the material. The education participants were 16 pregnant women who came to the Mayangan Health Center to conduct an integrated Antenatal Care examination. The result of community service activities is that pregnant women can understand and carry out integrated antenatal care examinations in accordance with the directions of health workers and the fulfillment of K1 and K4-K6 coverage targets in the work area of the Mayangan Jogoroto Jombang Health Center.